FORFEITS / PRICE COMPENSATED BY THE FORMER BAHAWALPUR STATE IN LIEU OF COALITION WITH THE BRITISH - Ali Asdullah, Dr. Samia Khalid, Gulzar Ahmad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The main objectives of the present study are to seek the contribution of the State ‎forces for the British which played a vital role to strengthen ‎British Raj in the subcontinent and in return to it, the Bahawalpur State had to pay a ‎huge price of the relations/alliances with the Government of British India to ‎show the faithfulness and loyalty. The historical and descriptive research method is utilized ‎and collected data from the different archives and libraries of Pakistan for the ‎accomplishment of the present paper which highlighted all the events and services ‎provided for the British by the State of Bahawalpur from 1833 to the emergence ‎of Pakistan. The State had to pay a huge price for its continued existence and had ‎to forgo many times for the British. It is also proved that the Bahawalpur State ‎not established relations with the Government of the British Empire on an egalitarian ‎basis. The State had to contribute in many expeditions just for the sake of ‎gratification and cheerfulness of his unofficial masters which provided evidence ‎of the loyalty and dependability of Bahawalpur State. All these ‎surrenders and forfeits tolerated by the State for the British Crown which played a ‎essential role in the intransigence and stability of the colonial period in the sub-continent.‎